Pharmacodynamic Target Assessment and PK/PD Cutoff Determination for Gamithromycin Against Streptococcus suis in Piglets - Wang, Rui-Ling; Liu, Ping; Chen, Xiao-Feng; Yao, Xin; Liao, Xiao-Ping; Liu, Ya-Hong; Sun, Jian; Zhou, Yu-Feng (Frontiers in Veterinary Science, 2022)
Gamithromycin is a long-acting azalide antibiotic that has been developed recently for the treatment of swine respiratory diseases. In the present study, the pharmacokinetic/pharmacodynamic (PK/PD) targets, PK/PD cutoff and optimum dosing regimen of gamithromycin were evaluated in piglets against S. suis in China, including a subset with capsular serotype 2. Short PAEs (0.5-2.6 h) and PA-SMEs (2.4-7.7 h) were observed for gamithromycin against S. suis. Serum matrix dramatically facilitated the intracellular uptake of gamithromycin by S. suis strains, thus contributing to the potentiation effect of serum on their susceptibilities, with a MHB/serum MIC ratio of 28.86 for S. suis. Dose-response relationship demonstrated AUC/MIC ratio to be the predictive PK/PD index closely linked to activity (R2 >0.93). For S. suis infections, the net stasis, 1-log10 and 2-log10 kill effects were achieved at serum AUC24h/MIC targets of 17.9, 49.1 and 166 h, respectively. At the current clinical dose of 6.0 mg/kg, gamithromycin PK/PD cutoff value was determined to be 8 mg/L. A PK/PD-based dose assessment demonstrated that the optimum dose regimen of gamithromycin to achieve effective treatments for the observed wild-type MIC distribution of S. suis in China with a probability of target attainment (PTA) ≥ 90% was 2.53 mg/kg in this study. These results will aid in the development of clinical dose-optimization studies and the establishment of clinical breakpoints for gamithromycin in the treatment of swine respiratory infections due to S. suis.